NEBULIZATION INTERVENTION OF ACUTE ASTHMA EXACERBATION IN EMERGENCY DEPARTMENT : A LITERATURE REVIEW - Dicky Endrian Kurniawan; Dewi Kartikawati Ningsih (Journal of Nursing Science Update (JNSU), 2017)
Â Acute exacerbation of asthma attack are often found in the emergency room. One of the interventions that can be administered is nebulization. The aim is to developed nebulization administration protocol that can be administer to the patients. A literature review are used from journal articles were obtained from search engineer such as Google.com and ScienceDirect.com. Nebulization was depending on the severity level of the patient conditions. The option of prepartions that can be used in a mixture nebulized are salbutamol, lidocaine, and heliox. Health providers (especially nurses) must be aware to the needs of the patient to the treatment options so it can be provided appropriately. Further research are needed to develop protocol intervention, so it can be applied in clinical setting.